General methodology for the chemoselective N-alkylation of (2, 2, 6, 6)-tetramethylpiperidin-4-ol: Contribution of microwave irradiation. Issue 3 (17th January 2019) - Membrat, Romain; Vasseur, Alexandre; Giordano, Laurent; Martinez, Alexandre; Nuel, Didier
Graphical abstract: Highlights: Alkylation of sterically hindered amines. N -Alkylation versus O -Alkylation. Microwave irradiation used to decrease reaction time. Microwave irradiation improves the yields. Abstract: A convenient method to access a broad variety of N -alkyl-(2, 2, 6, 6)-tetramethylpiperidin-4-ol compounds is reported. The thermal treatment of a mixture of (2, 2, 6, 6)-tetramethylpiperidin-4-ol and allyl or benzyl bromide derivatives gave the corresponding N –alkylated compounds in good yields while leaving the hydroxyl functional group intact. Whereas 40 h were needed to reach complete conversion, microwave irradiation allowed the reaction time to be reduced (20 min) and improved the yields in most cases.